Evaluación de los procesos productivos de la empresa Auto Talleres S.P.A. - Pila Chicaiza, Deysi Estefania (2023)
The present project of titulation has for object the Evaluation of the productive processes of the company Auto Talleres S.P.A, which is located in the city of Latacunga that is dedicated to the service of straightened and automotive painting, in addition, in the process of production the company counts on six ships of: Reception and waiting, straightening, preparation, painting, assembly and delivery. Such is the case that the company has little technical documentation on production processes, which details each of the activities that are immersed, and in fact by not having the necessary information about the processes, workers are prone to the risk of generating errors and failures, therefore, as a consequence affects the efficiency of the company and at the same time the decrease of customers. Therefore, the project investigative has the finality to determine the current conditions of the productive processes by means of a field investigation and with it to establish the current efficiency through analytical cursograms, in addition, to develop a proposal of improvement by means of the standardisation of productive processes that allows the increase of the efficiency. For which it was developed analytical cursograms classifying into 3 types of damage: mild, medium and strong was considered in this way because the damage can be caused of different magnitude, in this type of work can also be found all types of vehicle, brand, colour, year, etc., In this way to know the current status of the company and to obtain a standard time for each of them, and as a result we have a current efficiency of 84%, while identifying existing waste, being the activities that do not add value as well as: delays and reprocessing currently have an average of approximately 15% taking into account the 3 types of damage, for this reason the standardization decreased waste to approximately 7%, which allowed to obtain a future efficiency of 93%.